Taking stocks of antimalarial activities: A study on knowledge and skill of health personnel at primary care setting in the state of West Bengal, India - A B Biswas; Sarmila Mallik; Dipta Kanti Mukhopadhyay; Aditya Prasad Sarkar; Susmita Nayak; Asit Kumar Biswas (Wolters Kluwer Medknow Publications, 2016)
Background: Early diagnosis and effective treatment are the key areas in malaria control in India. Objective: The present study was carried out to assess the knowledge and skill of health personnel at primary care level and the logistic support related to the program at subcenter (SC) level. Methods: A cross-sectional, descriptive study was conducted among medical and paramedical personnel working at primary health-care institutions in two districts of West Bengal. Knowledge was assessed using a structured questionnaire while diagnostic skill and logistic support were assessed with structured checklists. Clinical skill was assessed with case vignettes. Results: Requisite knowledge on diagnostic procedure was found in two-third to three-fourth of health personnel while only 26.7% and 12.4%, respectively, knew the correct treatment of Plasmodium vivax and Plasmodium falciparum malaria. Median standardized score for knowledge was 50.0 while the scores for skill of preparing blood slide and for rapid diagnostic test were 70.0 and 57.1, respectively. Education and work experience were related to diagnostic skill but had little effect on knowledge. In clinical skill, medical personnel scored 50% or more in investigation and treatment aspects only. In another case vignette, health workers excelled over medical officers and other staff in all axes other than history taking and clinical examination although their performance was also suboptimal. Formal training on malaria did not show any bearing on median knowledge and skill score. Supply of diagnostics and drugs was insufficient in majority of SCs. Conclusion: Renewed efforts are needed to create competent workforce and ensure adequate logistic supply.